Determination of Mercury in Various Environmental Samples in 2012 - Narayana Suvarapu, Lakshmi; Seo, Young-Kyo; Baek, Sung-Ok (Asian Journal of Chemistry, 2013)
This paper discusses the determination of mercury in different biological and environmental samples with various analytical techniques, such as atomic absorption spectroscopy, spectrophotometer, voltammeter, inductively coupled plasma techniques, Spectrofluorometer and HPLC/GC reported by the researchers worldwide during 2012.